Leadership and risk-taking propensity among entrepreneurs in Malaysia / Ahmad Fadhly Arham and Norhayati Sulaiman - Sulaiman, Norhayati; Arham, Ahmad Fadhly (Faculty of Business Management, 2013)
The objectives of this paper are twofold. First, the author intends to explore on the form of leadership behaviours being practiced by leaders of SMEs in Malaysia. Second, this paper aims to explore on their risk-taking propensity. Based on semi-structured interviews among owners and top manager of SMEs, it was found that leaders of SMEs in Malaysia practice both transformational and transactional leadership. Leaders of SMEs in Malaysia also display more frequently the attributes of transformational leadership than transactional leadership. The interview data also revealed that leaders of SMEs in Malaysia are willing to take risks. They understand that being a risk taker supplements the entrepreneurs‟ level of innovativeness and proactiveness because without the dimension of risk-taking, it is very difficult for the entrepreneurial firms to invest heavily into the R&D and becoming the pioneers in the marketplace. This study is among the first to examine the type of leadership behaviours and risk-taking propensity of entrepreneurs in Malaysia from a qualitative perspective.